THE EFFECT OF COMPENSATION AND TRAINING ON WORK MOTIVATION WITH INDIVIDUAL CHARACTERISTICS AS A MODERATING VARIABLE AT PT PLN (PERSERO) UP3 PEMATANG SIANTAR - Rahmat Sihombing; Mesra B; Muhammad Isa Indrawan; Kiki Farida Ferine (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of compensation and training on work motivation with individual characteristics as moderating variables at PT PLN (Persero) UP3 Pematang Siantar. Work motivation is an important aspect in improving employee performance and organizational effectiveness, where compensation and training are seen as two main factors influencing it. Individual characteristics such as age, education, and work experience are assumed to strengthen or weaken the relationship. The research method used is quantitative with the Partial Least Square (PLS) approach to test the structural model. The research sample was 93 respondents who were employees in the customer service unit. The research instrument has met the validity and reliability tests, with outer loadings values above 0.70 and composite reliability above 0.90. The results show that compensation, training, and individual characteristics have a positive and significant effect on work motivation. However, individual characteristics do not play a significant role as moderating variables in strengthening the effect of compensation and training on work motivation. The R² value of 0.733 indicates that 73.3% of the variation in work motivation can be explained by this research model. These findings indicate that the management of PT PLN (Persero) UP3 Pematang Siantar needs to pay attention to providing quality compensation and training as a strategy to increase work motivation, even though individual characteristics do not significantly strengthen the relationship.